Principales tipo de contracción, efectos sobre el concreto y sus métodos de mitigación (2020)
The phenomenon of the shrinkage is one of the main factors that affect the durability of concrete, this is presented as a consequence of the loss of moisture generated in the processes of hydration of cement, in addition to the interference of internal factors, as the chemical composition of the components that make up the mixture, and external factors, whether environmental conditions or construction practices. The shrinkage of the concrete is divided primarily into three main stages: Autologous shrinkage, presented in the first hours of the hydration of the cement; plastic shrinkage, presented after 24 hours until the drying stage (28 days) and shrinkage from 28 days to 56 days. There are good practice recommendations to mitigate the negative consequences of total shrinkage at each of its stages, either by using proportions of components of the mixture appropriate to the composition of the cement, the water content-cement, additives for shrinkage reduction, the type of fine and coarse aggregate or, on the other hand, the appropriate use and implementation of steel reinforcement, location of construction joints, contraction joints, expansion joints and curing methods. Within the research it was found that in the mitigation practices of autologous shrinkage in the concrete a very effective option is the use of aggregates that allow the internal curing of the concrete, practice consisting of an internal supply of water thanks to saturated aggregates, other options use shrinking or expanding additives and even a combination of these. Methods to mitigate plastic shrinkage found that the use of polypropylene fibers as well as the use of additives as shrinkage reducers, potentially reduce the development of cracks, thanks to the fact that the fibers provide resistance to the contraction of the paste, in addition to a greater traction capacity. Finally, in the methods to mitigate drying contraction it was found that the reinforcement designs of the elements should be concentrated in critical stress areas such as the corners or edges of the cross sections; practice consisting of an internal supply of water thanks to saturated aggregates, other options use shrinking or expanding additives and even a combination of these. Methods to mitigate plastic shrinkage found that the use of polypropylene fibers as well as the use of additives as shrinkage reducers, potentially reduce the development of cracks, thanks to the fact that the fibers provide resistance to the contraction of the paste, in addition to a greater traction capacity. Finally, in the methods to mitigate drying contraction it was found that the reinforcement designs of the elements should be concentrated in critical stress areas such as the corners or edges of the cross sections; the use of reducing additives.